LEVEL OF KNOWLEDGE OF THE TAXPAYER IN THE LIQUIDATION OF THE SELECTIVE CONSUMPTION TAX - Daniel Fariña Colina, Richar; Gustavo Chaparro Acevedo, Sergio; Magali Bernal Alcaraz, Tamara (Revista Gênero e Interdisciplinaridade, 2023)
The tax is the tribute that a natural or legal person contributes to the State, whose objective is to cover public expenses, hence the importance of understanding the origin and why of taxes. Therefore, the selective consumption tax is a tax aimed at products that are not considered essential and also tend to act as environmental pollutants. When analyzing the ISC liquidation procedure, we realized the great relevance of knowing the level of knowledge that the Ciudad del Este taxpayer has about it. The Methodological approach developed is quantitative, the research design is non-experimental, cross-sectional, for which the survey was chosen as a data collection technique considering a population of 6 companies that operate in the area, using a sample of the 100% of the population. We see a medium level of knowledge of the procedure for liquidating the Selective Consumption Tax since the information is very basic in this regard.